Cognitive Impairments in Abstinent Male Residents of a Therapeutic Community for Substance-Use Disorders: A Five-Year Retrospective Study. (21st March 2019) - Shlosberg, Dan; Amit, Ben H.; Zalsman, Gil; Krivoy, Amir; Mell, Haim; Lev-Ran, Shaul; Shoval, Gal
Abstract: Background and Objectives: Prior studies of residual cognitive deficits in abstinent substance-use disorder (SUD) patients, exhibited conflicting reports and a substantial patient selection bias. The aim of this study was to test the cognitive function of a sample of chronic abstinent SUD patients in a therapeutic-community. Methods: The IntegNeuro TM cognitive test battery was used for a retrospective cross-sectional study of cognitive functioning of an unselected sample ( n = 105) of abstinent male residents of a therapeutic-community. The results were compared to a large age-, gender-, and education-matched normative cohort. Results: A significant negative deviance from the normal cohorts' mean was present in most of the cognitive test results and in all the cognitive domains that were tested. The most substantial deficit was found in the executive function domain ( d = 1.02, 95%CI (±0.11)). Correct identification of facial emotions was significantly lower selectively in expressions of disgust and sadness. Substance-use starting at an early age (12.4 ± 0.8 years) was associated with lower performance in tests of sustained attention and impulsivity as well as with varied ability to identify correctly "negative" emotions in the emotion identification domain. Conclusions: This 5-year retrospective study demonstrates substantial cognitive impairments in an unselected sample of abstinent SUD patients. Impairment in multiple cognitive domains may lower the probability for remission and successful social integration. Early-age substance initiation may be associated with larger impairments in cognitive performance.